2006
DOI: 10.1093/alcalc/agl016
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Motivational Interviewing as a Brief Intervention for Excessive Drinking: A Meta-Analytic Review

Abstract: Brief MI is effective. Future studies should focus on possible predictors of efficacy such as gender, age, employment status, marital status, mental health, initial expectations, readiness to change, and whether the population is drawn from treatment-seeking or non-treatment-seeking populations. Also, the components of MI should be compared to determine which are most responsible for maintaining long-term changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
365
1
19

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(401 citation statements)
references
References 35 publications
16
365
1
19
Order By: Relevance
“…Age also appears to be an important predictor of treatment outcome in BI, as shown by data from a meta-analytic review of the efficacy of these interventions [31]. Shakeshaft et al found that a brief motivational intervention was more efficacious among clients who were older at baseline, indicating that older participants in their study were more active in treatment and less likely to withdraw.…”
Section: Discussionmentioning
confidence: 97%
“…Age also appears to be an important predictor of treatment outcome in BI, as shown by data from a meta-analytic review of the efficacy of these interventions [31]. Shakeshaft et al found that a brief motivational intervention was more efficacious among clients who were older at baseline, indicating that older participants in their study were more active in treatment and less likely to withdraw.…”
Section: Discussionmentioning
confidence: 97%
“…MI is a method of clinical interaction that continues to receive significant interest in the addictions field and beyond (Carroll et al, 2006;Knight et al, 2006;Vasilaki et al, 2006). Defined as "a client-centered, directive method for enhancing intrinsic motivation to change by exploring and resolving ambivalence (p. 25)" (Miller and Rollnick, 2002), MI is grounded in the four principles of expressing empathy, developing discrepancy, rolling with resistance and supporting self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that workplace programs have the potential to support change in drinking norms and reduction of harmful drinking (e.g., Webb, Shakeshaft, Sanson-Fisher, & Havard, 2009), and that even brief interventions for harmful alcohol consumption have the potential to reduce alcohol intake (Kaner et al, 2007;Vasilaki, Hosier, & Cox, 2006). As a part of this strategy, special attention needs to be paid to treatment barriers that have been described in many other studies, such as concerns about privacy, social ------IJADR 7(1) ------stigma, and lack of social support systems (e.g., Grella & Stein, 2013;Schomerus et al, 2011;Schmidt & Room, 1999;Yap et al, 2013).…”
Section: Discussionmentioning
confidence: 99%